Health Education And Knowledge Of Dental And Oral Maintenance In Grade Ii (Two) Elementary School Cildren In Bantaeng District, South Sulawesi - Suardi, Vivi Adriana; Nurhaedah, Nurhaedah; Apulina, Endam; Herman, Herman; Latif, Farida (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Oral and dental health maintenance behavior should be carried out from an early age, the most appropriate time to instill values to form positive behavior is school age. Elementary school age is the ideal time to train a child's motor skills, including brushing teeth. In addition, school age has shown sensitivity to learning according to the child's curiosity. The purpose of the study was to determine the level of knowledge of Oral and Dental Health Maintenance of grade II (two) Elementary School children in Bantaeng Regency, South Sulawesi, to prevent dental and oral diseases, increase endurance, and improve oral function to increase appetite. Maintaining dental and oral hygiene at school age is one way to improve health at an early age. This research method is descriptive by providing a description of knowledge about dental health maintenance actions. The results of the study showed that students with a level of knowledge showed that almost all students in grade II (two) of Elementary Schools in Bantaeng Regency, South Sulawesi had good knowledge (92%). The conclusion obtained shows that there is a significant relationship between maternal knowledge and the provision of exclusive breastfeeding in the working area of ​​the Takalar Regency Health Center.Oral and dental health maintenance behavior should be carried out from an early age, the most appropriate time to instill values to form positive behavior is school age. Elementary school age is the ideal time to train a child's motor skills, including brushing teeth. In addition, school age has shown sensitivity to learning according to the child's curiosity. The purpose of the study was to determine the level of knowledge of Oral and Dental Health Maintenance of grade II (two) Elementary School children in Bantaeng Regency, South Sulawesi, to prevent dental and oral diseases, increase endurance, and improve oral function to increase appetite. Maintaining dental and oral hygiene at school age is one way to improve health at an early age. This research method is descriptive by providing a description of knowledge about dental health maintenance actions. The results of the study showed that students with a level of knowledge showed that almost all students in grade II (two) of Elementary Schools in Bantaeng Regency, South Sulawesi had good knowledge (92%). The conclusion obtained shows that there is a significant relationship between maternal knowledge and the provision of exclusive breastfeeding in the working area of ​​the Takalar Regency Health Center.